DIGITAL LITERACY AND EDUCATORS OF ISLAMIC EDUCATION - Sunarti Suly Eraku; Mohamad Karmin Baruadi; Samuel PD Anantadjaya; Siti Fadjarajani; Ucup Supriatna; Ardian Arifin (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
From the teacher's approach to students to the use of media in learning, the learning process has changed dramatically in this digital era. Islamic Religious Education teachers must improve their competence due to the stigma that they are